Monsha'at Sharia Financing for Saudi Arabia’s SMEs: A Case Study of Buraydah Specialty Coffee - Maspul, Kurniawan Arif (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
This revolutionary research reveals the spectacular rise of the specialty coffee sector in Al-Qassim, Saudi Arabia, and its profound impact on the region's economy. Al-Qassim has evolved as a dynamic specialty coffee hub, attracting worldwide coffee enthusiasts and supporting sustainable enterprises. Supported by Monsha’at's Sharia Financing principles, the specialty coffee sector has enjoyed extraordinary growth and sustainability, enabling Al-Qassim's small and medium-sized enterprises (SMEs). Buraydah, a UNESCO culinary city, is the hub of this specialty coffee trend. Collaboration among coffee businesses within and beyond Saudi Arabia, bolstered by global associations has further accelerated the industry's progress. This study provides valuable insights into the efficacy of Islamic finance in supporting SMEs and contributes to the advancement of Saudi Arabia's dynamic business environment. With its strategic advantages, supportive initiatives, and global connectivity, Al-Qassim is poised to become a dominant player in the regional and international coffee market, fueling economic prosperity and solidifying Saudi Arabia's position as a specialty coffee destination.